Analysis of Factors Affecting Gross Regional Domestic Product (GRDP) on the Island of Kalimantan 2014 – 2023 - Saputra, Irawan; Rusdi, Muhammad (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to identify the factors that affect the GRDP on the island of Kalimantan in the period 2014–2023. The data used is panel data from five provinces on the island of Kalimantan. The dependent variable in this study is GRDP, while the independent variables include domestic investment (DI), foreign investment (FDI), and labor force (LF). Data analysis was carried out using the panel data regression method. Based on the study's results, it was found that FDI did not significantly influence the GRDP on the island of Kalimantan. In contrast, domestic investment and labor force significantly influenced GRDP during the study period.